Transformational leadership and employee turnover intention : A study in a manufacturing based company in Malaysia - Sangeetha S. Amayappan, 1982- author; Ishak Mad Shah, supervisor; Fakulti Pengurusan (2013)
Thesis (Sarjana Sains (Pembangunan Sumber Manusia)) - Universiti Teknologi Malaysia, 2013